Ritual dan Eksistensi Ekologis: Kajian Ekokritik Terhadap Tradisi Lisan Dalam Ritual Ceriak Nerang Suku Jerieng - Fernanda, Andri; Ansyari, Irvan; Farhaby, Arthur Muhammad (eScience Humanity Journal, 2024)
This research aims to analyze the ecological existence of oral traditions in the Ceriak Nerang ritual of the Jerieng Tribe, Simpang Teritip District, West Bangka. In the village of Kundi Bersatu, West Bangka, the Ceriak Nerang ritual by the Jering tribe is precisely held. It can be seen that the continuity of the ritual becomes part of the preservation of the oral tradition as well as showing the ecological role in Jerieng tribe’s life. This research uses descriptive qualitative method by using gathered data from journals, magazines, and online media based on the analysis involved. The result of this research shows an overview of the description related to the fact, and how the sequences of the phenomena occur. Surprisingly, oral tradition plays a pivotal role not only for sharing the past event but also it helps to maintain the ritual of Ceriak Nerang which leads to preserve the nature of west Bangka.